MODEL PELITA SEBAGAI INOVASI MANAJEMEN PEMBELAJARAN PENDIDIKAN LINGKUNGAN HIDUP BERBASIS PLATFORM - Suhardi; Nurkulla, Muhammad Mashuri; Rahman, Hasan Basri; Rosyada, Dede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop the PELITA Model as a digital platform-based innovation for managing local content learning in Environmental Education (EE) in Kayong Utara Regency. The research employed the Design and Development Research (DDR) method, which consisted of needs analysis, model development and validation, implementation, and evaluation stages. The PELITA Model comprises six main components: Local Wisdom-Based Learning Planning, Digital Learning Ecosystem, Cultural and Technological Literacy, Integration of Local Learning Resources, Learning Quality Management, and Continuous Assessment. The results showed that the model achieved an average validity score of 4.71 (highly valid), a practicality level of 91.8% (highly practical), and effectively improved the quality of learning management. The integration of learning technology increased from 45.8% to 93.7%, while students’ learning mastery improved from 67.2% to 92.2%. These findings indicate that the PELITA Model is valid, practical, and effective in supporting the implementation of Environmental Education through the integration of educational management, digital technology, local wisdom, and a sustainable quality culture.